2022
DOI: 10.7554/elife.81703
|View full text |Cite
|
Sign up to set email alerts
|

Sugar sensation and mechanosensation in the egg-laying preference shift of Drosophila suzukii

Abstract: The agricultural pest Drosophila suzukii differs from most other Drosophila species in that it lays eggs in ripe, rather than overripe, fruit. Previously, we showed that changes in bitter taste sensation accompanied this adaptation (Dweck et al., 2021). Here, we show that D. suzukii has also undergone a variety of changes in sweet taste sensation. D. suzukii has a weaker preference than Drosophila melanogaster for laying eggs on substrates containing all three primary fruit sugars: sucrose, fructose, and gluco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 61 publications
4
13
0
Order By: Relevance
“…A large, serrated ovipositor is present on abdominal tip of D. suzukii females, which is pierced into the soft ripening fruit. The eggs are laid inside the fruit and the developing maggots consume the fruits and make them vulnerable to microbial infection [ 1 , 38 , 39 ]. In choice and no choice assays, our results showed that SA application on a fly diet resulted in reduced oviposition by D. suzukii in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large, serrated ovipositor is present on abdominal tip of D. suzukii females, which is pierced into the soft ripening fruit. The eggs are laid inside the fruit and the developing maggots consume the fruits and make them vulnerable to microbial infection [ 1 , 38 , 39 ]. In choice and no choice assays, our results showed that SA application on a fly diet resulted in reduced oviposition by D. suzukii in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Though, SWD females are least attracted to unripe fruits, they possess a nasty ovipositor to lacerate the immature or unripe fruits. Further, it has been reported that life history traits, fecundity, insecticide tolerance, etc., depend on sucrose concentrations in fruits [ 39 ]. The total soluble sugars influence the oviposition behavior of SWD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that ectopic expression of Ih in bGRNs also upheld SP and the activity of the neighboring sGRNs, underscoring the independent capability of HCN in SP preservation. Despite such an option available, the preference for sGRNs over bGRNs in HCN-mediated taste homeostasis implies that Drosophila melanogaster may have ecologically adapted to the high sweetness 52 prevalent in their feeding niche, such as overripe or fermented fruits 53 . It would be interesting to investigate whether and how respective niches of various insect species differentiate the HCN expression pattern in sensory receptor neurons for ecological adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in D. melanogaster and other drosophilids have revealed that oviposition decisions are complex, multisensory-dependent behaviors 35 , 52 , 55 , 56 , guided both by substrate properties and the recent experience of animals 57 ; moreover, the choice of egg-laying site is often assay-dependent (e.g., 58 , 59 ). Using several types of behavioral assays, we have confirmed the importance of noni for D. sechellia for egg-laying rate and site selection.…”
Section: Discussionmentioning
confidence: 99%